Juridical Study of the Authority of Psychologists in Psychological Examination of Members of the National Police Who Commit Disciplinary Violations in the Ranks of the Bali Police - Nyoman Tri Jaya Putra; Erikson Sihotang; Kadek Dedy Suryana (Jurnal Syntax Transformation, 2025)
The authority of psychologists in examining police members who commit disciplinary violations in the Bali regional police a) Helps identify problems that cause indisciplinary actions by police members. Police members are individual units that are also inseparable from problems in their daily environment. b) Helps in the form of counseling so as to reduce indisciplinary actions by police members. Related to the lack of awareness, compliance and implementation of police members towards their responsibilities as police members that bind them, it is necessary to carry out routine supervision by Siwas for general monitoring and supervision of the implementation of police leadership policies in the field of coaching and operations carried out by all work units. The obstacles faced by psychologists when examining police members who commit disciplinary violations in the Bali regional police are that superiors are not optimal in supporting counseling programs, lack of job desk arrangements for psychologists, budget factors, socialization factors and understanding factors of police members and psychologists. Meanwhile, the solution in the development of police psychology for members who commit disciplinary violations is the socialization of re-development of psychology to all members in the Bali Regional Police to prevent disciplinary violations, making regulations for the head of the Republic of Indonesia Police which stipulate that every superior is a counselor in order to meet the number of adequate psychological development.